2020
DOI: 10.1152/ajplung.00215.2020
|View full text |Cite|
|
Sign up to set email alerts
|

Phenylalanine induces pulmonary hypertension through calcium-sensing receptor activation

Abstract: Background: Phenylalanine levels are associated with pulmonary hypertension in metabolic profiling clinical studies. However, the pathophysiologic role of phenylalanine on pulmonary circulation is still unclear. We experimentally addressed the direct impact of phenylalanine on pulmonary circulation in rats and explored the underlying molecular pathway. Methods and results: Phenylalanine was injected intraperitoneally into Sprague-Dawley rats (400 mg/100g body weight) as a single dose or daily in a chronic mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Phenylalanine, when substantially increased, is recognized to be involved in numerous pathophysiological processes, such as chronic obstructive pulmonary disease, persistent pulmonary hypertension, and coronary heart disease . Tan et al demonstrated that chronic phenylalanine administration induced PAH through binding to the calcium-sensing receptor and its subsequent activation in rats . According to this finding, they proposed a hypothesis that phenylalanine probably accumulates in the lungs of PAH, which was not previously reported but was confirmed by our current work.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Phenylalanine, when substantially increased, is recognized to be involved in numerous pathophysiological processes, such as chronic obstructive pulmonary disease, persistent pulmonary hypertension, and coronary heart disease . Tan et al demonstrated that chronic phenylalanine administration induced PAH through binding to the calcium-sensing receptor and its subsequent activation in rats . According to this finding, they proposed a hypothesis that phenylalanine probably accumulates in the lungs of PAH, which was not previously reported but was confirmed by our current work.…”
Section: Discussionsupporting
confidence: 86%
“…53 Tan et al demonstrated that chronic phenylalanine administration induced PAH through binding to the calcium-sensing receptor and its subsequent activation in rats. 54 According to this finding, they proposed a hypothesis that phenylalanine probably accumulates in the lungs of PAH, which was not previously reported but was confirmed by our current work. Furthermore, tryptophan, an essential amino acid that could act as a precursor in serotonin production, was found to be upregulated in PAH PAs in our study.…”
Section: Discussionsupporting
confidence: 86%
“…90 A study by Tan et al has the opposite view, and phenylalanine could induce pulmonary hypertension via binding to and activating calcium-sensing receptors. 91 Phenylalanine could be converted into tyrosine in the body, and tyrosine is a precursor to the norepinephrine, epinephrine, and dopamine. 92 High levels of these stress hormones are associated with the increased risk of hypertension.…”
Section: Papermentioning
confidence: 99%
“…The mechanism of salvianolic acid B is different from that of GXNT, suggesting that the effect of GXNT on CaMKII may come from other active ingredients. In terms of ion channels, there were many compounds with calcium or potassium ion channel activities in vessels, including phenylalanine ( Tan et al, 2020 ), ferulic acid ( Zhou et al, 2017 ), and salvianolic acid B ( Lam et al, 2006 ), and more compounds had the activity in other cells, such as salvianolic acid A in cardiomyocytes ( Bao, 1993 ), isosalvianolic acid C ( Lin et al, 2019 ) in mast cells, and so on. In addition, compounds with calmodulin activity include phenylalanine ( VanScyoc et al, 2002 ), chlorogenic acid ( Tong et al, 2007 ), and salvianolic acid A ( Qiang et al, 2015 ), but only chlorogenic acid was reported to be related to endothelial calmodulin.…”
Section: Discussionmentioning
confidence: 99%